From Blue Sky Research to Problem Solving: A Philosophy of Science Theory of New Knowledge Production - Kilduff, Martin; Mehra, Ajay; Dunn, Mary B. (Academy of Management Review, 2011)
We examine rationalized logics developed within discourses of the philosophy of science for implications for the organization of new knowledge. These logics, derived from a range of philosophies (structural realism, instrumentalism, problem solving, foundationalism, critical realism) offer alternative vocabularies of motive, frameworks for reasoning, and guidelines for practice. We discuss the kinds of knowledge produced, the indicators of progress, the characteristic methods, exemplar organizations, and ways in which logics are combined and diffused.